2021
DOI: 10.3324/haematol.2021.279631
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape of high-grade B-cell lymphoma with <i>MYC-</i>, <i>BCL2</i> and/or <i>BCL6</i> rearrangements characterized by whole-exome sequencing

Abstract: High-grade B-cell lymphoma accompanied with MYC and BCL2 and/or BCL6 rearrangements (HGBL-DH/TH) poses a cytogenetically-defined provisional entity among aggressive B-cell lymphomas that is traditionally associated with unfavorable prognosis. To better understand the mutational and molecular landscape of HGBL-DH/TH we here performed whole-exome-sequencing and deep panel next-generation-sequencing (NGS) of 47 clinically annotated cases. Oncogenic drivers, mutational signatures and perturbed pathways were compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 52 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…However, the present meta-analysis did demonstrate an improved 2y-PFS using intensified regimens over R-CHOP (-like) (HR=0.66; p=0.045). Interestingly, one study included in this meta-analysis showed improved 2y-PFS with R-CHOP(-like) protocols (26). This is possibly explained by selection bias as these patients were older (median age 73 vs. 60 years), had less frequently advanced stage disease (47.6% vs. 92.3%), and less often concomitant BCL2 translocation (52.4% vs. 76.9%), signifying an enrichment in the pathogenetically and clinically divergent MYC/ BCL6 rearranged subgroup.…”
Section: Figurementioning
confidence: 91%
See 2 more Smart Citations
“…However, the present meta-analysis did demonstrate an improved 2y-PFS using intensified regimens over R-CHOP (-like) (HR=0.66; p=0.045). Interestingly, one study included in this meta-analysis showed improved 2y-PFS with R-CHOP(-like) protocols (26). This is possibly explained by selection bias as these patients were older (median age 73 vs. 60 years), had less frequently advanced stage disease (47.6% vs. 92.3%), and less often concomitant BCL2 translocation (52.4% vs. 76.9%), signifying an enrichment in the pathogenetically and clinically divergent MYC/ BCL6 rearranged subgroup.…”
Section: Figurementioning
confidence: 91%
“…The flowchart of the reviews shows the detailed process of selection (Figure 1). Finally, 11 relevant studies, comprising a total of 891 HGBCL-DH/TH patients, were included (6,7,18,(25)(26)(27)(28)(29)(30)(31)(32). We identified no prospective, randomized controlled trials (RCT); all studies included in the meta-analysis were of retrospective design.…”
Section: Study Selection and Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to DLBCL or HGBCL with MYC and BCL2 rearrangements, it shows GCB immunophenotype less often, is more likely to be CD10(−)/IRF4/MUM1(+), infrequently expresses BCL2 and is cytogenetically less complex [ 144 ]. Moreover, it does not show the impairment of TP53 and MYC signaling pathway typically observed in DLBCL or HGBCL with MYC and BCL2 rearrangements, whereas it exhibits impairment of E2F targets [ 148 ]. Because of its less distinctive biological features [ 141 ], HGBCL with MYC and BCL6 rearrangements, regarded as a provisional entity in ICC, is considered in the WHO-HAEM5 as a genetic subtypes of DLBCL, NOS and HGBCL, NOS, respectively.…”
Section: Mature B-cell Neoplasmsmentioning
confidence: 99%
“…In MCL, concurrent TP53 and CDKN2A gene aberrations correlate with chemoresistance [50]. In BL, we already assessed the prognostic role of MYC insertions or concomitant BCL2 and BCL6 mutations [46,51]. In B-ALL/LBL and HGBL with MYC and BCL2 and/or BCL6 rearrangements, NGS sequencing has shown recurrent variants of genes coding for transcription factors (MYC, FOXO1), epigenetic modulators (KMT2D, EZH2, and CREBBP), and antiapoptotic proteins (BCL2) [51,52].…”
Section: Molecular Testingmentioning
confidence: 99%